Analisis Morfofisiologi, Anatomi, dan Histokimia pada Lima Spesies Tanaman Gulma sebagai Respons terhadap Merkuri dan Timbal - Rani Apriyani Raharja; Hamim Hamim; Yohana Caecilia Sulistyaningsih; Triadiati Triadiati (Jurnal Ilmu Pertanian Indonesia, 2020)
Plants can be used as phytoremediation agents to improve critical land due to gold mining activities. This experiment aimed to analyze the morphophysiological, anatomical, and histochemical responses of Brachiaria mutica, Cyperus kyllingia, Ipomea aquatica, Mikania micrantha, and Paspalum conjugatum in response to the application of heavy metals mercury and lead in the forms of Hg(NO3)2 and Pb(NO3)2 in hydroponic experiments and to determine the ability of these plants to accumulate both metals. Morphological responses were observed by measuring number of leaves and plant dry weight, and physiological responses were observed by analyzing photosynthetic pigments, while anatomical and histochemical responses were analyzed by microscopic observation to tranversal slice of roots and leaves. The results showed that the applications of Hg(NO3)2 and Pb(NO3)2 treatments caused decreases in number of leaves, plant dry weights, and photosynthetic pigments (chlorophyll a, chlorophyll b, and carotenoid). The treatments also decreased leaf thickness due to the decrease in the epidermis, but they caused the increases in exodermis and endodermis of the roots. Mercury and lead were accumulated in large amounts in the roots, but accumulation in the shoot was less. Histochemical observation showed that lead was found in the roots of all the plants, especially in endodermic tissue and the vessel, whereas in the leaves the two metals were detected in the upper and lower epidermis, mesophyll, and vessel. Among the five species tested, C. kyllingia and P. conjugatum were the most tolerant to Pb and Hg.